Analysis of The Effect of Indendence and Organizational Commitment on Auditor Performance at The Jayapura City Inspectorate Office - Ambriani Amir; Entar Sutisman; Sahrul Ponto (Westscience Press, 2023)
This study aims to obtain empirical evidence and analyze the effect of organizational commitment on auditor performance at the Jayapura City Inspectorate Office. This research is a type of research that tests hypotheses that aims to examine the relationship between the dependent variable, namely auditor performance, with the independent variables of organizational commitment and independence. In data collection, questionnaires were used as the main instrument through field studies at the Jayapura City Inspectorate Office of Papua Province. Research is descriptive with a quantitative approach, focusing on analyzing numerical data to get accurate conclusions. The research period was carried out for 3 months, from November 2023 to January 2024, involving all auditors at the Jayapura City Inspectorate Office. The results showed that increasing organizational commitment and auditor independence at the Jayapura City Inspectorate Office significantly contributed to improving auditor performance